Partially desulfated heparin modulates the interaction between anti-protamine/heparin antibodies and platelets - Jouni, Rabie; Zöllner, Heike; Khadour, Ahmad; Wesche, Jan; Grotevendt, Anne; Brandt, Sven; Delcea, Mihaela; Krauel, Krystin; Schwertz, Hansjörg; Sachs, Ulrich J.; Greinacher, Andreas; Bakchoul, Tamam (Thrombosis and Haemostasis, 2016)
Protamine (PRT) is the standard drug to neutralise heparin. PRT/heparin complexes induce an immune response similar to that observed in heparin-induced thrombocytopenia (HIT). Partially desulfated heparin (ODSH) was shown to interfere with anti-platelet factor 4/heparin antibodies (Abs), which are responsible for HIT. In this study, we analyse the impact of ODSH on the interaction between anti-PRT/heparin Abs and platelets. The ability of ODSH to prevent anti-PRT/heparin Ab-induced platelet destruction in vivo was investigated using the NOD/ SCID mouse model. ODSH improved platelet survival in the presence of PRT, heparin and anti-PRT/heparin Abs (median platelet survival after 300 minutes (min) with 20 μg/ml ODSH: 75 %, range 70–81 % vs without ODSH: 49%, range 44–59%, p=0.006). Furthermore, when ODSH was applied 60 min after Ab injection platelet survival was improved (median platelet survival after 300 min with ODSH: 83 %, range 77–93 % vs without ODSH: 59 %, range 29–61 %, p=0.02). In in vitro experiments ODSH inhibited platelet activation at concentrations > 16 μg/mL (p< 0.001), as well as PRT/heparin complex binding to platelets (mean fluorescence intensity [MFI] without ODSH: 85 ± 14 vs with ODSH: 15 ± 0.6, p=0.013). ODSH also displaced pre-bound complexes from the platelet surface (MFI without ODSH: 324 ± 43 vs with 32 μg/ml ODSH: 53 ± 9, p< 0.001). While interfering with platelet activation by anti-PRT/heparin Abs, up to a concentration of 16 μg/ml, ODSH had only minimal impact on neutralisation of heparin by PRT. In conclusion, our study shows that ODSH is able to inhibit platelet activation and destruction suggesting a potential clinical use to reduce anti-PRT/heparin Ab-mediated adverse effects.
Keywords: Thrombocytopenia; platelet immunology; animal models; heparins